2018
DOI: 10.1029/2017gl076717
|View full text |Cite
|
Sign up to set email alerts
|

The Unprecedented 2016–2017 Arctic Sea Ice Growth Season: The Crucial Role of Atmospheric Rivers and Longwave Fluxes

Abstract: The 2016–2017 Arctic sea ice growth season (October–March) exhibited one of the lowest values for end‐of‐season sea ice volume and extent of any year since 1979. An analysis of Modern‐Era Retrospective Analysis for Research and Applications, Version 2 atmospheric reanalysis data and Clouds and the Earth's Radiant Energy System radiative flux data reveals that a record warm and moist Arctic atmosphere supported the reduced sea ice growth. Numerous regional episodes of increased atmospheric temperature and moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 37 publications
3
62
0
Order By: Relevance
“…Despite the importance of ARs in moisture transport and of their influence on Arctic warming for example, [31] and on the extent of sea ice [27,28], their influences on the region have not yet been deeply investigated in relation to the terms pointed out here. Some studies have investigated the moisture sources for ARs from a Eulerian [32] or a Lagrangian point of view for different regions in Europe for example, [33][34][35], North America [36][37][38] and South Africa [39]; however, as far as we know, no such studies have been performed for the Arctic region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of ARs in moisture transport and of their influence on Arctic warming for example, [31] and on the extent of sea ice [27,28], their influences on the region have not yet been deeply investigated in relation to the terms pointed out here. Some studies have investigated the moisture sources for ARs from a Eulerian [32] or a Lagrangian point of view for different regions in Europe for example, [33][34][35], North America [36][37][38] and South Africa [39]; however, as far as we know, no such studies have been performed for the Arctic region.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested the influence of cyclones and ARs on the extent of sea ice across the Arctic region. Hegyi and Taylor [27] have demonstrated that episodic Arctic ARs actively contribute to the evolution of Arctic sea ice during the ice growth season. Moreover, Komatsu et al [28] investigated the influence of Siberian ARs entering the Arctic and noted an amplification of warming over the region in summer.…”
Section: Introductionmentioning
confidence: 99%
“…This amplification of warming in the Arctic is caused by several feedback mechanisms. Among them are the reduced sea ice extent and high sea surface temperature (Serreze et al, 2011;Hegyi and Taylor, 2018), changes in atmospheric circulation are typical for periods of warm and moist intrusions. Since the author investigated only on a short period, an analysis of longer cloud observations is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to precipitation at the climatological level, Lavers and Villarini ()) estimate that 30–50% of European and U.S. winter season precipitation is contributed by AR especially over their west coasts but note that there is much regional and monthly dependency of this association, whereas Dettinger () suggests that ARs are consequential as drought busters. The importance of AR for the cryosphere has also been noted with respect to ablation rates over Greenland (Mattingly, Mote, & Fettweis, ; Neff, ); snowfall and ablation in New Zealand (Little, Kingston, Cullen, & Gibson, ), East Antarctica (Gorodetskaya, Tsukernik, & Claes, ), and the western United States (Guan, Molotch, & Waliser, ); the transport of moisture and energy to the Arctic Ocean Basin (Hegyi & Taylor, ; Villamil‐Otero, Zhang, He, & Zhang, ); and climate variability and change in extratropical and high latitudes (Nash, Waliser, Guan, Ye, & Ralph, ).…”
Section: Atmospheric Riversmentioning
confidence: 96%